Penggunaan Software Akuntansi Accurate 5 Sebagai Penunjang Penyusunan dan Penyajian Laporan Keuangan Klien - Fiinaa Maghfirotuzzahro; Wulan Suryaningsih; Aditya Agung Nugraha (Journal of Economics and Business Research (JUEBIR), 2023)
This research aims to comprehensively analyze the utilization of the accounting software Accurate 5 in the process of preparing and presenting financial reports for clients at Andita Gunawan Accounting Firm in Tegal City. The research methodology employed is a case study, with data collection conducted through in-depth interviews and direct observations. This qualitative research utilizes a descriptive approach and falls under the category of field research, supported by a review of existing literature. The findings of the study reveal that the implementation of Accurate 5 significantly enhances efficiency in the preparation of financial reports, reduces the potential for human errors, and overall improves the accuracy of financial information. Furthermore, this software empowers the accounting firm to provide more professional services to its clients, establishing higher standards of quality. In conclusion, the use of the Accurate 5 accounting software has a positive impact on supporting the preparation and presentation of financial reports for clients at Andita Gunawan Accounting Firm in Tegal City. It contributes significantly to enhancing the effectiveness and reliability of accounting processes within the firm's environment.